Facile Electro-Assisted Green Synthesis of Size-Tunable Silver Nanoparticles and Its Photodegradation Activity - N. S., Kamarudin; R., Jusoh; N. F., Sukor; A. A., Jalil; H. D., Setiabudi; N. F. M., Salleh (Springer, 2022)
An eco-benign procedure was developed to synthesize ultrafine and discrete spherical shape silver nanoparticles (5–20 nm) in the presence of ionic liquid. Different types of leaves extract, including Cymbopogon nardus, Polygonum minus, Allium Cepa, and Petroselinum crispum, were used as a green reducing and capping agents for the synthesis process. The Ag nanoparticles were denoted as AgCN, AgPM, AgAC, and AgPC, respectively. Notably, it was demonstrated that the Ag nanoparticles' size could simply be altered by varying the amount of total phenolic content (TPC) using different leaves. It was indicated from the characterization results that the AgPC nanoparticles’ size was nine-fold smaller compared to the conventional Ag nanoparticles due to the high amount of total phenolic compounds (TPC) in the Petroselinum crispum. The results also revealed that ionic liquid and phenolic compounds had a synergistic effect on reducing silver ions (Ag+) into silver nanoparticles (Ag) and the stabilization of the nanoparticles. The order obtained for the degradation of methylene blue (MB) was AgPC > AgPM > AgCN > AgAC > Ag was influenced by a large amount of TPC and led to a decrease in particle size and enhanced photocatalytic activity. The AgPC remained effective and stable even after five subsequent cycles.